Commentary: Reflections on the COVID-19 Pandemic and Health Disparities in Pediatric Psychology. (8th August 2020) - Valenzuela, Jessica; Crosby, Lori E; Harrison, Roger R
Abstract: The COVID-19 (2019 novel coronavirus) pandemic has had a significant economic, social, emotional, and public health impact in the United States. A disturbing trend is that Black, Indigenous, and/or People of Color (BIPOC) are disproportionately contracting coronavirus, as well as dying from COVID-19. Objective/Methods The pandemic has the potential to entrench and magnify existing health disparities and families marginalized across multiple demographic intersections such as race/ethnicity, class, immigration status, are especially vulnerable. These inequities have been further underscored by the recent murders of Black Americans by police and a resulting spotlight on racial injustice in the United States. Results Efforts to lessen the spread of the virus, have resulted in changes in pediatric primary and subspecialty service delivery which may affect access for BIPOC communities. BIPOC trainees including those with debt or caregiving responsibilities may be faced with new barriers resulting in delays in completion of their training. Further, clinical, community-based, and translational research has been disrupted by heightened safety precautions and social distancing which may affect BIPOC representation in research downstream. Conclusion In our roles as clinicians, supervisors, trainees, and researchers in primary and subspecialty care as well as in academia, pediatric psychologists have an ethical responsibility to address the disproportionate burden of this pandemic on vulnerable communities and to allocate our time and resources to ensuring health equity now and in the aftermath of COVID-19.